2016
DOI: 10.1016/j.cub.2016.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Individual Neuronal Subtypes Exhibit Diversity in CNS Myelination Mediated by Synaptic Vesicle Release

Abstract: SummaryRegulation of myelination by oligodendrocytes in the CNS has important consequences for higher-order nervous system function (e.g., [1, 2, 3, 4]), and there is growing consensus that neuronal activity regulates CNS myelination (e.g., [5, 6, 7, 8, 9]) through local axon-oligodendrocyte synaptic-vesicle-release-mediated signaling [10, 11, 12]. Recent analyses have indicated that myelination along axons of distinct neuronal subtypes can differ [13, 14], but it is not known whether regulation of myelination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
214
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(228 citation statements)
references
References 41 publications
11
214
1
2
Order By: Relevance
“…Following up on pioneering work (Barres & Raff, 1994; Demerens et al, 1996), electrical axonal activity and release of synaptic vesicles have been proposed recently as a major axonal signal modulating oligodendrogenesis, regulating the numbers and lengths of internodes generated, guiding the selection of axons to be myelinated, and adjusting the growth of myelin sheaths (Gibson et al, 2014; Hines, Ravanelli, Schwindt, Scott, & Appel, 2015; Koudelka et al, 2016; Mensch et al, 2015; Wake et al, 2015; Wake, Lee, & Fields, 2011). The molecular players underlying such activity‐dependent myelination are not univocally defined.…”
Section: Myelination and Mtormentioning
confidence: 99%
“…Following up on pioneering work (Barres & Raff, 1994; Demerens et al, 1996), electrical axonal activity and release of synaptic vesicles have been proposed recently as a major axonal signal modulating oligodendrogenesis, regulating the numbers and lengths of internodes generated, guiding the selection of axons to be myelinated, and adjusting the growth of myelin sheaths (Gibson et al, 2014; Hines, Ravanelli, Schwindt, Scott, & Appel, 2015; Koudelka et al, 2016; Mensch et al, 2015; Wake et al, 2015; Wake, Lee, & Fields, 2011). The molecular players underlying such activity‐dependent myelination are not univocally defined.…”
Section: Myelination and Mtormentioning
confidence: 99%
“…Multiple studies have shown that myelin deposition is not static, but far more dynamic than initially thought, with adaptive changes in myelin driven by changes in neuronal activity (myelin plasticity) (6,(20)(21)(22)(23)(24)(25). These changes, e.g., induced by optogenetic stimulation or stimulated through learning of complex motor skills, promote oligodendrogenesis and the deposition of new myelin sheaths along the axons.…”
Section: Introductionmentioning
confidence: 99%
“…Given that neuronal activity can regulate multiple stages of oligodendrocyte lineage 499 behaviour through myelination as well as axonal structure, it is likely that myelinated axon plasticity 500 plays a central role in many aspects of the formation and function of neuronal circuits that remain to 501 be discovered. activity-regulated myelination has been shown to be a property of only specific neuronal subtypes 514 (Koudelka et al, 2016). It will be important to define which neurons and circuits exhibit myelinatedaxon plasticity throughout life, and in response to experience.…”
mentioning
confidence: 99%